2017
DOI: 10.5152/tjbh.2017.3342
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Lifestyle Interventions in Breast Cancer Women after Completion of Primary Therapy: A Randomized Study

Abstract: IntroductionA number of risk factors have been identified in the pathogenesis of breast tumors. Among these, a great number of factors are attributed to the lifestyle (1). Reduced physical activity during cancer treatment can decrease the capacity for physical conditioning. The late effects of cancer and its treatment may consequently reduce physical activity in survivors. Breast cancer survivors with sedentary lifestyle have a higher risk for early mortality (2).About 20%-70% of breast cancer survivors may ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(50 citation statements)
references
References 20 publications
1
48
0
1
Order By: Relevance
“…The characteristics of study populations, intervention protocols and outcome measures and tools of measure are briefly described. All 57 selected studies, all RCTs in their design and published between 2001 and 2020 [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characteristics of study populations, intervention protocols and outcome measures and tools of measure are briefly described. All 57 selected studies, all RCTs in their design and published between 2001 and 2020 [ 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , …”
Section: Resultsmentioning
confidence: 99%
“…In addition, we showed that concurrent training had a moderate positive effect on fatigue in women with breast cancer during active treatment (d = −0.59, 95% CI −0.79 to −0.38; I 2 = 62.5%). Furthermore, the eight trials employing different forms of intervention combining aerobic plus resistance interventions and aerobic or resistance training alone with a volume ≥150 min/week [ 32 , 33 , 40 , 41 , 46 , 47 , 51 , 67 ] demonstrated significant effect sizes across various fatigue scales. This is an important finding, because the beneficial effects of exercise interventions for both patients in active treatment (chemotherapy or radiation) and breast cancer survivors have been previously reported [ 82 , 83 , 84 , 85 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[17] In a research by Ghavami and Akyolcu, Cronbach's alpha reliability coefficient of the Persian version of PSQI scale (α) in the first measurement was 0.746 and it was calculated as 0.783 in the last evaluation. [18] Also, Farrahi Moghaddam et al . in 2012 realized Cronbach's alpha coefficient of 0.89% for the Persian version of PSQI.…”
Section: Methodsmentioning
confidence: 99%
“…In the study of Ghavami and Akyolcu, Cronbach's alpha reliability coefficient of the Persian version of the PSQI scale (a) in the first measurement was calculated as 0.746 and it was 0.783 in the last measurement. [13] Furthermore, Farrahi Moghaddam et al [14] reported a sensitivity of 100%, specificity of 93%, and a Cronbach's alpha coefficient of 0.89% for the Persian version of the questionnaire. The PSQI and DIF were filled for all the participants before the intervention.…”
Section: Data Collection and Measurementsmentioning
confidence: 99%